THE NEED OF PEER COUNSELLING TOWARDS MENTAL HEALTH AMONG UNIVERSITY STUDENTS IN A PUBLIC UNIVERSITY, SELANGOR - Sham, Fatimah; Badrulhisyam, Nur Khairunnisa; Fauzi, Rosuzeita; Nordin, Roswati; Azamuddin, Ain Aqiela (Journal of Islamic, Social, Economics and Development, 2024)
University students globally face significant mental health challenges. Peer counselling, offering support like professional counselling, bridges gaps in mental health resources, enhancing coping skills and social connections. This approach addresses barriers like stigma and limited access to traditional mental health services. The specific objectives were to determine the prevalence of stressors, the effect of mental health, the common stressors, the preference coping mechanism related to stress/psychological issues, help-seeking behavior and the barrier to seeking help for psychological issues. A quantitative, descriptive cross-sectional study was conducted among 784 students in a public university, Selangor from December 2023 and May 2024. The research tool used in this study is the self-administrated questionnaire, developed and validated for this research. Most of the respondents preferred to seek help from their peers (40.2%; n: 315) compared to the professional counselor (28.7%; n: 225). The most barrier seeking help were concerns about what others think (83.3%) and feelings of shame (79.5%). Current findings showed most students prefer talking to their peers over seeking professional counselling, though stigma and shame often prevent them from seeking help at all. Encouraging peer counselling could help reduce stigma and make it easier for students to seek help.